Real-world effectiveness and safety of 1L polyethylene glycol and ascorbic acid for bowel preparation in patients aged 80 years or older - Machlab, Salvador; Lorenzo-Zúñiga, Vicente; Pantaleon, Miguel Angel; Sábado, Fernando; Arieira, Cátia; Pérez Arellano, Elena; Cotter, José; Carral, David; Turbí Disla, Carmen; Gorjão, Ricardo; Esteban, Jose Miguel; Rodriguez, Sarbelio (Endoscopy International Open, 2025)
Clinical trials and real-world studies show a 1L polyethene glycol and ascorbic acid solution (1L PEG-ASC) to be an effective and safe bowel preparation for colonoscopy in the general population. Here, the effectiveness and safety of 1L PEG-ASC were evaluated in patients aged 80 years or older in a real-world setting.A post-hoc analysis of an observational, multicenter, retrospective study assessed the effectiveness and safety of 1L PEG-ASC on outpatients aged ≥ 80 years old undergoing colonoscopy at eight centers in Spain and Portugal. Cleansing quality was assessed using the Boston Bowel Preparation Scale, with overall scores ≥ 6 and all segmental scores ≥ 2 considered adequate colon cleansing, and overall scores ≥ 8 or 3 in the right colon considered high-quality cleansing. Cecal intubation rate, withdrawal time, polyp and adenoma detection rates (ADR), and adverse events (AEs) were also monitored.Data were analyzed from 423 patients aged ≥ 80 years; mean age 83.5 years (±3.2) and 49.2% males. The adequate colon cleansing success rate was 88.9%, with high-quality cleansing of the overall and right colon achieved in 54.1% and 46.1% of patients, respectively. Colonoscopy was complete in 94.1% of cases and the ADR was 51.3%. At least one AE was experienced by 4.5% of participants, the most frequent being mild dehydration (2.8%) and nausea (1.2%).This post-hoc analysis confirms 1L PEG-ASC to be an effective and safe bowel cleansing preparation for patients aged 80 years or older in a real-world setting.
Keywords: Quality and logistical aspects; Preparation; Endoscopy Small Bowel; Performance and complications